INVENTARISASI JENIS-JENIS POHON PENEDUH DI DALAM KAWASAN KAMPUS BINA WIDYA UNIVERSITAS RIAU SEBAGAI SUMBER BELAJAR PADA KONSEP KEANEKARAGAMAN HAYATI DI SMA - Fajri, Fajri; Nursal, Nursal; Fauziah, Yuslim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims to inventory the types of shade trees in the area of Riau University road and provide a source of learning about the diversity of plants concept in senior hig school. This study used survey method is to do an inventory of the types of road shade trees located along the main road in the campus area of the University of Riau and has been carried out in December 2013 to February 2014. Parameters used in this study is biological parameters such as the diversity, dominance by canopy cover, plant phenology, and botanical description of the way that the dominant shade trees in the campus area Bina Widya University of Riau and physical parameters namely temperature and humidity. The results showed that the composition of shade plants found in 5 study locations in Bina Widya campus area as many as 30 species of plants from 16 familia and diversity index in the region of Riau University Bina Widya campus area ranged from0.77 until 2.34 with medium category. The highest diversity index at the fourth location is 2.34 and the lowest was on location V is 0.77. Shade treea type domination in Bina Widya campus is mahoni. Shade trees phenology in Bina Widya campus generaliy green leafy.Keywords: inventory, shade trees, learning resources